Bertrand Russell and Catalan Literature: In Praise of Idleness and Other Essays and Dictionary for the Idle - Gonçal López-Pampló Rius (Interlitteraria)
Joan Fuster (Sueca, 1922–1992) was one of the most important essayists of Catalan literature. Diccionari per a ociosos (Dictionary for the Idle), published in 1964, has been widely seen as one of his masterpieces, not only because of the wide range of topics he deals with, but also because of his witty and contemporary insight. Despite this critical acclaim, many aspects of this book still deserve further research. In this article we try to study more deeply the sources of Dictionary for the Idle, focusing on Bertrand Russell’s In Praise of Idleness and Other Essays (1935). Beyond the similar titles, we think that Joan Fuster could have been inspired by Russell’s literary style and intellectual attitude, not only because of stylistic and thematic similarities, but also because of the attested references (among which we will comment on which of Russell’s books are kept in Fuster’s personal library). A direct rewriting between In Praise of Idleness… and Diccionari per a ociosos must be dismissed due to lack of written proof, as well as direct allusions, which do not appear whatsoever. However, our aim is to trace the link between these two authors and the influence that the former had on the latter, in the context of his general influence on both Spanish and Catalan contemporary essay.